Tinjauan Hukum Dagang Dalam Permohonan Pailit Pada Badan Usaha Milik Negara (BUMN) Dan Akibat Hukum Pada BUMN Pailit - Firdaus, Muhammad Irkham; Reyhan, Muhammad (Fakultas Hukum Universitas Primagraha, 2024)
BUMN is a legal entity that is independent and autonomous like other private legal entities. So that BUMN can seek profits (profit oriented) and can also experience losses from the business activities carried out. This research aims to discuss whether a BUMN can be declared bankrupt and what conditions are needed to file a bankruptcy declaration for a BUMN according to Law No. 37 of 2004. This research uses a qualitative research method with a normative approach. And the form of this research is library research, so the data is taken from book literature, journals, laws and websites. The result of this research is that debt owned by BUMN can be paid through a bankruptcy mechanism in accordance with the requirements determined by UUKPKPU. UUKPKPU does not recognize differences in bankruptcy regulations between BUMN and private legal entities, so BUMN are also subject to UUKPKPU bankruptcy regulations. The requirements for bankruptcy of a company are regulated in Article 2 paragraph (1) UUKPKPU. Law Number 37 of 2004 concerning Bankruptcy and Postponement of Debt Payment Obligations states that the Minister of Finance is the only party who can file a bankruptcy statement for BUMN operating in the public sector. BUMN declared bankrupt by the Commercial Court will have legal consequences for the parties concerned.